AFRICAN HUMAN MOBILITY REVIEW - Crush, Jonathan (African Human Mobility Review, 2021)
On a recent visit to Washington DC, I had an animated discussion with a taxidriver who was an avid supporter of Donald Trump. The driver was not thestereotypical white, middle-aged, small-town, working-class, non-collegeeducated,angry voter who put Trump in the White House. Rather, he was aformer television producer and poet from India who had immigrated to theUS in the 1990s, and was adamant that Trump would stop the â€œflood of illegalaliensâ€ into the country. His vigorous defence of Trump was a surprise, as washis buy-in to Trumpâ€™s anti-immigrant discourse of threat. There are few issuesin the contemporary world that generate so much uninformed debate andmisinformation as immigration (Blinder, 2015; de Haas, 2008; Hellwig andSinno, 2017; Valentino et al., 2013).